A multi-user remote academic laboratory system (2013)
This article describes the development, implementation and preliminary operation assessment of Multiuser Network Architecture to integrate a number of Remote Academic Laboratories for educational purposes on automatic control. Through the Internet, real processes or physical experiments conducted at the control engineering laboratories of four universities are remotely operated. Through an internet connection to the Manager Administration Server, a remote experiment to design and test a modeling and control algorithm can be performed. The suggested Network Architecture is based on the Singlet-Server model and uses a database server to record important information that helps create a new remote experiment, including a Graphical User Interface (Applet) developed with Easy Java Simulation, which allows the simple integration of new processes to the Manager Administrator. Results of a real-physical-process remote manipulation through the proposed network architecture are presented as well as results of an academic pilot test conducted to measure functional aspects related to the operation of the remote system when carrying out remote-laboratory work. © 2012 Elsevier Ltd. All rights reserved.